New insight on study of Ni-base alloy clad layer after oxidation at 650 °C. (1st April 2019) - Solecka, Monika; Radziszewska, Agnieszka; Rutkowski, Bogdan
Graphical abstract: Highlights: TEM-ASTAR method was used for phase mapping of oxides formed on the Ni-base alloy. Oxide scale consist mostly of NiO in outer zone, Cr2 O3 in inner zone and NiCr2 O4 in between. Phase- and chemical composition provide evidence for the protective values of the formed oxide scale. Abstract: The investigation was carried out on the Ni-based alloy (Inconel 625) clad layer after oxidation at a temperature of 650 °C for a duration of 2000 h in an atmosphere of ash from a waste incineration plant. The characterization of the oxide scale was performed using phase mapping technique (ASTAR) of transmission electron microscopy. The investigation revealed formation of two-layered continuous passive oxide scale on the surface of the superalloy. Its outer zone is built from NiO and inner zone is composed mainly of Cr2 O3 . Between the above mentioned oxide layers, the NiCr2 O4 spinel and NbCrO4 oxide have been observed.